Database of Agroclimatic Indices in Honduras (1981-2022): Historical Record of Dry Conditions, Heatwaves, and Water Availability Across Agricultural Seasons. - Barrios Pérez, Camilo; Amaya Quintero, Alejandra (2023)
The dataset consists of spatial information with a grid resolution of 0.05°, providing historical agroclimatic indices related to dry conditions, extreme heat, and water availability during the agricultural seasons (Primera, Canícula, Postrera, and Apante) in Honduras. Spanning from 1981 to 2022, it includes eight indices categorized into Dry Conditions (Number of Dry Days, Number of Dry Spells, Average Length of Dry Spells),